Comparison of Angiographic Severity between Patients of Acute Myocardial Infarction & Chronic Stable Angina Pectoris (University Heart Journal, 2012)
A prospective randomized cohort study was done in 100 patients and the study population consisted 50 patients with unheralded acute myocardial infarction and 50 with uncomplicated stable angina pectoris. The main objectives of the study were to compare the angiographic severity between the two clinical subsets of IHD. The study observed that regarding number of vessels diseased , the AMI group had 1.52±0.68 compared with 2.37±0.85 vessels for the angina group reflecting significantly higher diseased vessel in latter group (P